Integration of somatosensory and motor-related information in the auditory system - Lohse, Michael; Zimmer-Harwood, Paul; Dahmen, Johannes C.; King, Andrew J. (Frontiers in Neuroscience, 2022)
An ability to integrate information provided by different sensory modalities is a fundamental feature of neurons in many brain areas. Because visual and auditory inputs often originate from the same external object, which may be located some distance away from the observer, the synthesis of these cues can improve localization accuracy and speed up behavioral responses. By contrast, multisensory interactions occurring close to the body typically involve a combination of tactile stimuli with other sensory modalities. Moreover, most activities involving active touch generate sound, indicating that stimuli in these modalities are frequently experienced together. In this review, we examine the basis for determining sound-source distance and the contribution of auditory inputs to the neural encoding of space around the body. We then consider the perceptual consequences of combining auditory and tactile inputs in humans and discuss recent evidence from animal studies demonstrating how cortical and subcortical areas work together to mediate communication between these senses. This research has shown that somatosensory inputs interface with and modulate sound processing at multiple levels of the auditory pathway, from the cochlear nucleus in the brainstem to the cortex. Circuits involving inputs from the primary somatosensory cortex to the auditory midbrain have been identified that mediate suppressive effects of whisker stimulation on auditory thalamocortical processing, providing a possible basis for prioritizing the processing of tactile cues from nearby objects. Close links also exist between audition and movement, and auditory responses are typically suppressed by locomotion and other actions. These movement-related signals are thought to cancel out self-generated sounds, but they may also affect auditory responses via the associated somatosensory stimulation or as a result of changes in brain state. Together, these studies highlight the importance of considering both multisensory context and movement-related activity in order to understand how the auditory cortex operates during natural behaviors, paving the way for future work to investigate auditory-somatosensory interactions in more ecological situations.